Exploring social determinants of health and their influence on quality of life and social welfare in Indonesia: a comprehensive review - Husni Thamrin; Hatta Ridho; Izzah Dienillah Saragih; Gusti Pirandy (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: This research examines the social deter-minants of health in Indo-nesia, with particular con-cern for how socioecono-mic inequalities affect public health and the social welfare. Objective: The main aim is to explore how the deter-minants (eg, education, income, access to health service, as well as envi-ronmental condition) influence quality of life and social well being among distinct population groups in Indonesia. Methodology: A scoping review approach was used to appraise the evidence base, across peer-reviewed journals, government policy documents and reputable media sources published in the last five years. Both qualitative and quantitative content analysis was used. Discussion: Socioeconomic status/ poverty, geo-graphic isolation and edu-cational disparities are found to be major barriers to the access and outcome of healthcare. Rural com-munities have even lower poverty; even less access to health care facilities; and fewer infrastructure facilities, compounded by health disparities. Furt-hermore, poor incorpora-tion of mental health into public health policy is a significant gap. Conclusion: Tackling the multi-dimensional pro-blems of social determi-nants is required to achieve health equity in Indonesia. Policymakers should invest in interven-tions tailored to particular contexts, particularly in rural areas, and focused on education, access to health care, infrastructure deve-lopment and mental health integration.